Young People and the Environment
XIV, 184 p.
Keywords: The book analyses the knowledge, beliefs and behaviours that comprise the environmental attitudes of young people in the Asia-Pacific region and the cultural, political and educational contexts that have shaped them. The findings are based upon a questionnaire survey of over 10,000 young people together with focus group studies in India, South China, Japan, Thailand, Singapore, Hong Kong, Brunei, Indonesia, Australia, New Zealand, Fiji, and the west coast of the USA.